Study of medical methods of abortion and self-attempted abortion - Kapadia, Labdhi M.; Mewada, Bhavna N.; Patel, Akash J.; Vaghela, Zeel R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Medical abortion in the early stages of pregnancy is considered safe, but it relies on having accurate information and support from a qualified healthcare professional. Despite this, many women opt to use medical abortion pills independently or with the assistance of unqualified practitioners, or pharmacists, as these drugs are readily available over-the-counter without requiring a medical prescription. Methods: This retrospective analytical study was undertaken at the department of obstetrics and gynaecology, at Smt. SCL municipal general hospital, Ahmedabad between December, 2022 to December, 2023. Results: The present study clearly suggests 50% cases of self-attempted medical abortion with drug purchased ‘over the counter’ needs surgical evacuation, 30% managed with further medical intervention and blood transfusion, while comparing with cases which were prescribed MTP Pills in tertiary health care centre need surgical intervention in only 10% cases and the complete abortion rate was 90%. Conclusions: In India the drugs for medical abortion are easily available and accessible without prescription, so most women feel it can be carried out in privacy and they only come to hospital when they develop complications. When MTP pills are prescribed under care of properly trained healthcare personnel with proper guidelines, they have a high success rate and fewer complications.